2020
DOI: 10.1007/s00125-020-05287-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between family history, early growth and the risk of beta cell autoimmunity in children at risk for type 1 diabetes

Abstract: Aims/hypothesis The aim of this work was to examine the relationship between family history of type 1 diabetes, birthweight, growth during the first 2 years and development of multiple beta cell autoantibodies in children with a first-degree relative with type 1 diabetes and HLA-conferred disease susceptibility. Methods In a secondary analysis of the Trial to Reduce IDDM in the Genetically at Risk (TRIGR), clinical characteristics and development of beta cell autoantibodies were compared in relation to famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…Our results are different from the TEDDY study, where children with increased genetic risk for T1D were leaner than the general population [14]. However, increased height and weight gain in childhood have been found to be associated with the development of islet autoimmunity or T1D, supporting the accelerator hypothesis [2,18,19]. Children who developed diabetes before 6 years of age were significantly taller from 6 to 18 months of age when corrected for MPH [3].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are different from the TEDDY study, where children with increased genetic risk for T1D were leaner than the general population [14]. However, increased height and weight gain in childhood have been found to be associated with the development of islet autoimmunity or T1D, supporting the accelerator hypothesis [2,18,19]. Children who developed diabetes before 6 years of age were significantly taller from 6 to 18 months of age when corrected for MPH [3].…”
Section: Discussioncontrasting
confidence: 99%
“…It is also in agreement with our finding of negative association of height and development of islet autoimmunity by age 8 years. In the TRIGR study, the risk of islet autoimmunity with multiple autoantibodies was positively associated with the child’s height velocity during the first 2 years of life ( 24 ). In the DAISY study, greater height growth velocity of children over 2 years of age was associated with both increased risk of islet autoimmunity and type 1 diabetes ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pacaud et al, in a secondary analysis of the TRIGR study, compared the clinical characteristics and development of β-cell autoantibodies in patients with a family history of T1DM. The research involved 2074 children from families with a single family member (mother, father, or sibling) affected by T1DM [ 54 ]. The study showed that the risk to develop β-cell autoimmunity was significantly lower ( p < 0.001) in children with maternal T1DM than with other family members with T1DM.…”
Section: Quaternary Preventionmentioning
confidence: 99%